2010
DOI: 10.1093/carcin/bgq097
|View full text |Cite
|
Sign up to set email alerts
|

G 12/13 inhibition enhances the anticancer effect of bortezomib through PSMB5 downregulation

Abstract: Bortezomib is a proteasome inhibitor approved for anticancer therapy. However, variable sensitivity of tumor cells exists in this therapy probably due to differences in the expression of proteasome subunits. G(alpha)(12/13) serves modulators or signal transducers in diverse pathways. This study investigated whether cancer cells display differential sensitivity to bortezomib with reference to G(alpha)(12/13) expression, and if so, whether G(alpha)(12/13) affects the expression of proteasome subunits and their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…41 Cell culture Huh7, HepG2, SK-Hep1 and SNU449 cells were cultured as described previously. 14,42 Stable transfection of the active mutant of Gα 12 (Gα 12 Q229L, Gα 12 QL) was carried out previously. 14 To establish Gα 12 -depleted SK-Hep1 cells, oligonucleotides for the generation of shRNA were designed as follows: control (luciferase) 5′-GGATCCGCGGTTGCCAAGAGGTT CCATTTCAAGAGAATGGAACCTCTTGGCAACCGCTTTTTTGGAAAGCTT-3′; and Gα 12 , 5′-GGATCCGCGACACCATCTTCGACAACATTTCAAGAGA ATGTTGTCGA AGATGGTGTCGCTTTTTTGGAAAGCTT-3′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Cell culture Huh7, HepG2, SK-Hep1 and SNU449 cells were cultured as described previously. 14,42 Stable transfection of the active mutant of Gα 12 (Gα 12 Q229L, Gα 12 QL) was carried out previously. 14 To establish Gα 12 -depleted SK-Hep1 cells, oligonucleotides for the generation of shRNA were designed as follows: control (luciferase) 5′-GGATCCGCGGTTGCCAAGAGGTT CCATTTCAAGAGAATGGAACCTCTTGGCAACCGCTTTTTTGGAAAGCTT-3′; and Gα 12 , 5′-GGATCCGCGACACCATCTTCGACAACATTTCAAGAGA ATGTTGTCGA AGATGGTGTCGCTTTTTTGGAAAGCTT-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Gα 12 miRNome and integrative analysis of miRNA and mRNA changes To understand the effect of Gα 12 overexpression on the pathophyiology of HCC and establish a cellular model system in vitro, we used an HCC cell line stably transfected with a constitutively active (CA) Q229L mutant of Gα 12 (Gα 12 QL) as a tool. 13,14 Of the widely used liver tumor cell lines, we first used Huh7 because it has low Gα 12 expression, and subjected wild-type (WT)-Huh7 and Gα 12 QL-Huh7 to the miRNA microarray assays ( Figure 2a). Volcano plot shows the relationship of changes in miRNA expression between the two groups with significance (Supplementary Figure S1a).…”
Section: Gα 12 Overexpression In Hccmentioning
confidence: 99%
“…In this respect, another study reported that repression of PSMB5, PSMB10, and PA28α sub-units sensitized hepatocellular carcinoma cells to bortezomib. 97 STAT3 is a transcription factor activated down-stream of several receptor tyrosine kinases, including EGFR, and cytokine receptors (Figure 7). It is activated in several cancer cell types and has been shown to up-regulate several β sub-units of the 20S proteasome.…”
Section: Rbx1mentioning
confidence: 99%
“…Therefore, over-expression of the PSMB5 gene in response to drug stress, contributing to the increased chymotrypsinlike activity, is an important mechanism of acquired bortezomib resistance. Study of Yang YM et al demonstrated that the PSMB5 downregulation by Ga12/13 inhibition enhances the anticancer effect of bortezomib, which may be of use to improve bortezomib therapy and reduce bortezomib resistance [31]. Former study by Kraus et al showed that the proteasomal activity profile varies in primary leukemia cells, and that the pattern of proteasomal subunit activity influences the sensitivity of hematologic malignancies toward bortezomib [32].…”
Section: Introductionmentioning
confidence: 99%